IMPLEMENTASI MANAJEMEN MUTU MADRASAH ALIYAH SWASTA AL-WASHLIYAH 30 BINJAI - Yahfizham Yahfizham; Miswanto Miswanto; Sitie Budisuku; Sumitra Dewi; Shopiana Shopiana (Universitas Dharmawangsa, 2020)
The implementation of quality management in Madrasah Aliyah Al-Washliyah 30 Binjai is done by collaborating with all teachers and the school community, but teachers have an important role in fostering the morals of students through the learning process. Before teaching teachers make plans in the form of lesson plans, and in the implementation of learning the teacher becomes an example for students, the teacher always instills a disciplined attitude in learning, teaches respect for others and instills a sense of responsibility to study hard. In addition, the teacher conducts an evaluation by observing and asking questions to find out the quality management application at Madrasah Aliyah Al-Washliyah 30 Binjai. The results of the implementation process of Islamic Religious Education learning in fostering the morals of students in Madrasah Aliyah Al-Washliyah 30 Binjai were not achieved optimally. The teacher has made a plan but in the implementation of learning does not match expectations as obstacles. Some students have good character, but there are still students who lack discipline because of the influence of family and environment.